Pulverização dirigida no sulco e inoculação na semente de milho com Azospirillum brasilense - Lopes, Marlo Markus (2016)
The present work aimed to evaluate the influence of different methods of plant growth promoting bacterium (PGPB) Azospirillum brasilense inoculated at vegetative development and grain yield of corn in different relief zones. The research was carried in Cruzeiro do Sul (RS) with mechanized sowing of Velox TL® very early hybrid corn, in the 2015/2016 harvest. The treatments were: seed Inoculation and nitrogen fertilization (T1); directed spraying in furrow and nitrogen fertilization (T2); and control, only with nitrogen fertilization (T3). The experimental design was a factorial 3x3, considering three inoculation methods (seed inoculation, directed spraying in furrow and no inoculation) and three relief zones (high, medium and low levels), with three replications. The following variables were determinate: plant height, stem diameter, total dry matter and number of grains per plant. The data were submitted to the Tukey test, at 5% probability of error level. There was no interaction between inoculation methods and relief zones. Both directed spraying in furrow and corn seed inoculation with diazotrophic bacterium Azospirillum brasilense provided only a higher final average height of the plants, when compared to the traditional management, without the use of seed inoculation. Thus, Azospirillum brasilense promotes greater height development of Velox TL® hybrid corn, without, however, influence on stem diameter, total dry matter and number of grains per plant. Stem diameter variable was influenced by relief zones, which presents greater development in the average zone in comparison to the low zone, demonstrating the importance of precision agriculture that not consider areas as being homogeneous.